Effectiveness of Using E-Magazine Learning Media on Soup Material in Continental Food Courses - Anugerah, Ajeng Inggit; Akmal, Nikmat; Rahmi, Ana; Waruwu, Mawadda Azizah Sari (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aimed to evaluate the effectiveness of using E-Magazine as a learning media in Continental Food course, focusing on Soup material. This study used a quasi-experimental design involving 60 students, who were divided into two groups: an experimental group using the E-Magazine, and a control group using a conventional textbook. The E-Magazine was designed to provide interactive materials such as recipes, cooking techniques, and demonstration videos. Data were obtained through student engagement questionnaires and knowledge tests and before and after learning. The analysis results showed that the experimental group had a higher engagement mean score of 4.6, with a Standard deviation of 0.5%. Compared to the control group with an average score of 3.3 with a standard deviation of 0.4%. In addition, there was a significant increase in knowledge scores after learning in the experimental group (mean pretest = 63, mean post test = 87) compared to the control group (mean pretest = 61, and posttest = 74). The t-test showed significant differences between the two groups on both student engagement (t (62) = 5.12, p < 0.001) and knowledge (t (62) = 6.45, p < 0.001). This study shows that the use of E-Magazine can significantly increase student engagement and understanding in learning Soup material.Keywords: Learning Media, E-Magazine, Soup, Continental.